Reformulación de los surfactantes de una base de maquillaje para la obtención de una fórmula más natural (2020)
This study seeks to reformulate the surfactants of a foundation makeup in order to reduce the environmental and health negative impact. In this way, it is obtained a natural formula which is more attractive to the consumer. In order to achieve the objective, it is necessary to find out a formulation of a foundation makeup to vary the type and amount of surfactants in the five different reformulations that are carried out. It is important to highlight that the preparation conditions were the same for all the cases. Then, these formulations are tested for stability, viscosity, use and color analysis. Based on the results obtained, it is evident that it is possible to reformulate the foundation makeup using surfactant A and co-emulsifier A2, obtaining a formulation which is healthier and eco-friendly. However, the foundation makeup color is significantly altered by the replacement of the surfactant in the new formulation.